Dummy Decal: Contemporary Ceramics and Endless Decorative Creative Work - HASSAN, ZULKARNIAN; Noor Othman, Noor Ashraf; Md Nazri, Haslinda; Jasni Adie, Yasmeen Arni Jr. (Idealogy Journal; Vol 3 No 2 (2018): Idealogy Journal (September 2018)DO - 10.24191/idealogy.v3i2.76, 2018)
Regardless of the type of product or the differences in its basic elements, the product graphic is synonymous with high beauty, uniqueness, and precision. It is parallel with the beautiful ornaments that adorn the surface of the ceramic product, which originate from diverse civilizations and reflect the maker's creative inspiration. The decal is based on the most advanced and widely used ceramic decoration techniques in Europe and China, which serves as an inspiration for the rest of the globe when it comes to putting decoration to their products. Whichever is the case, the manufacturing and distribution expenses of decal decoration techniques are considerable, needing extensive preparation and execution to provide a high-quality result. As a result, the invention of the 'Dummy Decal' decoration process has enabled manufacturers of ceramic products to maintain a consistent level of output while adding differentiation to their designs. Water Based Inkjet Water Transfer Paper is a fresh source of inspiration for creative items and ceramic works. With a modest access fee and the ability to purchase, this decoration serves as a magnet for contemporary products and creative works. This article can be used as a guide and resource for small and medium-sized businesses, as well as individuals, to assist them in developing their creative thinking when it comes to marketing their organic products. Keyword: Ceramics, dummy decals, unique products, and décor